Benchmarking antibody clustering methods using sequence, structural, and machine learning similarity measures for antibody discovery applications - Chomicz, Dawid; Kończak, Jarosław; Wróbel, Sonia; Satława, Tadeusz; Dudzic, Paweł; Janusz, Bartosz; Tarkowski, Mateusz; Deszyński, Piotr; Gawłowski, Tomasz; Kostyn, Anna; Orłowski, Marek; Klaus, Tomasz; et al. (Frontiers in Molecular Biosciences, 2024)
Antibodies are proteins of our immune system that have been harnessed as biotherapeutics. The discovery of antibody-based therapeutics relies on analyzing large volumes of diverse sequences coming from phage display or animal immunizations. Identification of suitable therapeutic candidates is achieved by grouping the sequences by their similarity and subsequent selection of a diverse set of antibodies for further tests. Such groupings are typically created using sequence-similarity measures alone. Maximizing diversity in selected candidates is crucial to reducing the number of tests of molecules with near-identical properties. With the advances in structural modeling and machine learning, antibodies can now be grouped across other diversity dimensions, such as predicted paratopes or three-dimensional structures. Here we benchmarked antibody grouping methods using clonotype, sequence, paratope prediction, structure prediction, and embedding information. The results were benchmarked on two tasks: binder detection and epitope mapping. We demonstrate that on binder detection no method appears to outperform the others, while on epitope mapping, clonotype, paratope, and embedding clusterings are top performers. Most importantly, all the methods propose orthogonal groupings, o ering more diverse pools of candidates when using multiple methods than any single method alone. To facilitate exploring the diversity of antibodies using di erent methods we have created an online tool CLAP available at (clap.naturalantibody.com) that allows users to group, contrast, and visualize antibodies using the di erent grouping methods.